2018
DOI: 10.1002/rcs.1932
|View full text |Cite
|
Sign up to set email alerts
|

Motion modelling and error compensation of a cable-driven continuum robot for applications to minimally invasive surgery

Abstract: The established model and the proposed compensation method can be used for the cable-driven continuum robot to guarantee safety and stability in MIS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…According to the Kane's method, 26 the dynamic model can be established when the virtual power P of the external forces and moments is zero, as shown in Equation (). Assuming that the external force and moment of each segment are Fi,ex,Mi,ex, and based on the corresponding linear, angular velocity and acceleration, the dynamic model of the continuum robot is shown in Equation ().…”
Section: Dynamic Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…According to the Kane's method, 26 the dynamic model can be established when the virtual power P of the external forces and moments is zero, as shown in Equation (). Assuming that the external force and moment of each segment are Fi,ex,Mi,ex, and based on the corresponding linear, angular velocity and acceleration, the dynamic model of the continuum robot is shown in Equation ().…”
Section: Dynamic Analysismentioning
confidence: 99%
“…So the friction of the cable‐pulley system will inevitably affect the tension transmission of the driving cable, which impacts the control performance of the continuum robot. Therefore, the friction of the cable‐pulley system is briefly analysed in this section, which has been studied in our paper 26 …”
Section: Numerical Simulationmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to overcome the disadvantages of the traditional articulated rigid robot, we proposed a novel modular cable‐driven continuum robot in previous research, which is shown in Figure . The continuum robot consists of a super‐elastic NiTi alloy backbone fixed at the distal (tip) disk, a silicone shell, space disks, which can achieve the shape deformation by adapting the length of each driving cable.…”
Section: Robot Structure and Kinematicsmentioning
confidence: 99%